Hubungan Tingkat Pengetahuan Ibu Tentang Karies Gigi Dan Asupan Lemak Dengan Kejadian Karies Gigi Anak Balita Di Desa Mranggen Sukoharjo - Yuniati, Retno Dwi; , Endang Nur W, S.St., M.Si.Med; , Muwakhidah, SKM, M.Kes (2015)
Introduction: Dental caries is one of thooth health problems especially in children. Dental caries is an infection disease that can undermine the structure of teeth and causes cavities. Factors affecting dental caries in toddlers are knowledge of mother about dental caries and fat intake. Objective:This study aimed to determine the relationship between knowledge level of mothers about dental caries and fat intake and the occurrence of dental caries in toddlers in the village of Mranggen, Sukoharjo. Research method: Types of research used in this research was an observational with cross-sectional design. Subjects of this research were toddlers, and used the mothers as respondents. The sampling technique used simple random sampling. Statistical analyzes used chi-square tests. The data on occurrence of dental caries were obtained from examination conducted by a team of dentistry and the level of mothers knowledge about dental caries data were obtained through a questionnaire. Meanwhile, fat intake data were obtained by interviewing mothers using semi-quantitative food frequency method. Results: Most toddlers had dental caries (64,2%), knowledge level of mothers about dental caries mostly was poor (64,2%) and 51,9% of subjects had normal intake of fat. Correlation test for the relationship between knowledge level of mothers about dental caries and dental caries showed p value = 0,003 and the association between fat intake and dental caries showed p value = 0,114. Conclusion: There was a relationship between knowledge level of mothers about dental caries and the occurrence of dental caries, but there was no relationship between fat intake and the occurrence of dental caries in toddlers at the village Mranggen, Sukoharjo.